Et Tu, Zimmerman? Is Foreknowledge Useful After All? - Hasker, William (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2024)
Dean Zimmerman is an open theist. However, he has constructed an argument to the effect that, if simple foreknowledge (foreknowledge without middle knowledge) did exist, this knowledge would be providentially useful to God. I show that his argument fails: if simple foreknowledge did exist, it would be providentially useless.